Viewpoints on driving of individuals with and without autism spectrum disorder. (February 2015) - Chee, Derserri Yan-Ting; Lee, Hoe Chung-yeung; Falkmer, Marita; Barnett, Tania; Falkmer, Olov; Siljehav, Jessica; Falkmer, Torbjörn
Abstract Objective: Understanding the viewpoints of drivers with autism spectrum disorder (ASD) is crucial in the development of mobility support and driver training that is responsive to their needs. Methods: Fifty young adults with ASD and fifty seven typically developed adults participated in the study to form a contrasting group. Q-methodology was used to understand viewpoints on driving as a main mode of transportation. Data were analysed using a PQ by-person varimax rotation factor analysis. Results: Although some ASD participants perceived themselves as confident and independent drivers, others preferred other modes of transportation such as public transport and walking. Anxiety was also found to be a barrier to driving. The contrast group revealed consistent viewpoints on their driving ability. They preferred driving as their main mode of transportation and believed that they were competent, safe and independent drivers. Conclusion: These results are important in the planning of transport policies and driver training for individuals with ASD. Driver training manuals can be developed to address anxiety issues, hazard perception and navigation problems in the ASD population. Their use of public transport could be further facilitated through more inclusive transport policies.